2005
DOI: 10.1124/jpet.105.089946
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Third Intracellular Loop of the δ-Opioid Receptor Inhibits Signaling by Opioid Receptors and Other G Protein-Coupled Receptors

Abstract: To explore the feasibility of developing inhibitors of signaling by opioid receptors and other G protein-coupled receptors (GPCRs) that use the same G protein pool, we investigated the capacity of a minigene encoding the third intracellular loop of the ␦-opioid receptor (␦-i3L) to act as competitive antagonist of the receptor-G protein interface interaction. In ␦-i3L-expressing cells, the peptide blocked high-affinity agonist binding to both the ␦-and the -opioid (␦-OR and -OR) and attenuated opioid and ␣ 2 -a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…These observations are consistent with those of other groups using a similar experimental approach with other GPCRs, such as -opioid, µ-opioid and 2 -adrenergic receptors [29]. Upon co-expression of the minigene with the M 5 subtype, we also noted low affinity levels with agonist-stimulated […”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These observations are consistent with those of other groups using a similar experimental approach with other GPCRs, such as -opioid, µ-opioid and 2 -adrenergic receptors [29]. Upon co-expression of the minigene with the M 5 subtype, we also noted low affinity levels with agonist-stimulated […”
Section: Discussionsupporting
confidence: 80%
“…Coexpressing the minigene construct with the wild-type receptor decreased G protein activation, phosphatidylinositol production, and subsequent signaling, without effecting normal ligand binding and receptor membrane expression. Our results showed that co-expression of the 3ILoop of the M 3 receptor with the M 5 subtype are similar to previous studies of the 3ILoop of the µ-opioid receptor, which altered the functionality of the intact µ-opioid receptor as well as other classes of GPCR [29].…”
Section: Discussionsupporting
confidence: 79%
“…Previous experiments evidenced that co-expression of GPCR intracellular loops (or peptides derived from these loops) could mimic the intact receptor, interacting with the same molecular partners (Abdulaev et al, 2000;Morou and Georgoussi, 2005). In order to define protein complexes within GPCRs, we modified a TAP method suitable for the purification of associated proteins of the muscarinic acetylcholine receptor family (mAChRs), chosen as a model.…”
Section: Introductionmentioning
confidence: 99%
“…and Zioudrou [14]. proteins was verified by immunoblotting using the appropriate anti-223 bodies as described previously [24]. Protein samples were subjected to SDS-PAGE and electroblotted to 226 PVDF membranes.…”
mentioning
confidence: 99%
“…200 nM of U-255 50,488H was added to the cells and allowed to incubate at 37°C for 256 the indicated times. Measurement of MAPK phosphorylation was 257 performed as described by Morou and Gergoussi[24].…”
mentioning
confidence: 99%